(untitled) (Research, Society and Development, 2025)
Rheumatic fever is a late complication in predisposed individuals as an immune response to tonsillitis, mainly caused by Streptococcus pyogenes. The disease develops due to an autoimmune reaction of the host’s immune system against streptococcus, resulting in chronic valve and joint lesions. The diagnosis is made using the Jones criteria, including major and minor signs and evidence of previous streptococcal infection. Treatment involves prophylaxis with benzathine penicillin G in the acute phase to prevent chronicity and the development of rheumatic fever, treatment for carditis or arthritis consists of controlling symptoms with corticosteroids, anti-inflammatory drugs or surgery in severe cases. Therefore, this cross-sectional study aims to determine the epidemiological profile of pediatric patients with rheumatic fever in Bahia in the last 10 years, observing how epidemiology could determine the target population for public health policies. The study searched the Mortality Information System of the Unified Health System’s Information Technology Department, where the variables municipality of care, care regime, color/race, age group, and sex were analyzed. The quantitative profile and outline of the most affected population favor creating public policies and targeting budgets that allow for prevention and improvement in the service of this target group.